National and transnational paths of Latin American Jews : modernity, community, society, and the state - Bokser de Liwerant, Judit (Jewish identities in a changing world, 2025)
"This book has been conceived through sustained research and work with axioms, hypotheses, theories, findings, and inspiring dialogues that converge in building a conceptual pathway. Various levels of theoretical, empirical, and analytical approaches intersect, shaping a transversal trajectory in which the thematic variety finds common foundations in analyses that transit between theoretical abstraction and concrete reality, with a call for reflexivity. Approaching the study of Jewish life in Latin America in terms of the past-present timeline that shapes the dynamics of interaction between national/transnational dimensions allows for recovering traits of a trajectory and experiences while also making it possible to account for the current historical and conceptual transformations. On its part, a conceptual trajectory is marked by time and context-biography and history meet.